Impact of Destination Image on Tourists Satisfaction: A Case Study of Lake Bunyonyi Kigezi. - Tumwebaze, Ambrose (Kabale University, 2024)
This study aimed at the impact of destination image on tourist satisfaction. A case study of Lake Bunyonyi in the Kigezi region. Destination image is a perception people have of a certain place in an area. Tourist satisfaction is the experience and services the tourists get after getting to the destination you have visited. They inform, interpret, educate, interact, and communicate with tourists about the destination, its history, culture, local/host community, and the nature of the destination. The objectives of the study were to find out the cognitive image of tourist satisfaction. To find out the effects of a cultural image on tourist satisfaction. To establish the effects of an economic and social image on tourist satisfaction around Lake Bunyonyi within kigezi region. A population of 64 respondents was targeted, however, a sample size of 37 was used. Research methods that questionnaire method and interview guide were used a researcher constructed a relevant and straight-forward questionnaire for great ease of respondents. The findings on the impact of destination image on tourist satisfaction. There is limited research examining the relationship between its destination image and the satisfaction levels of tourists. The knowledge may hinder efforts to optimize the destination's appeal and enhance the experience of visitors.